2017
DOI: 10.5539/elt.v10n3p128
|View full text |Cite
|
Sign up to set email alerts
|

A Questionnaire-based Study on Chinese University Students’ Demotivation to Learn English

Abstract: This paper, adopting questionnaire survey method, investigated 367 non-key local university English as a Foreign Language (EFL) students' demotivation to learn English. The collected data revealed that there were two main categories of demotivators: internal factors (lack of intrinsic interest, experience of failure and lack of confidence, and unclear study goal) and external factors (teaching material, teaching process and teaching content, significant others, teachers' teaching competence and attitude of tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 7 publications
0
30
1
Order By: Relevance
“…Nevertheless, the studies of Sakai and Kikuchi (2009) revealed 'lack of intrinsic motivation' to be one of the most salient demotivating factors. In addition, a study of Li and Ting (2017) confirmed 'lack of intrinsic motivation' as the most demotivating factor. The findings of Ghadirzadeh and Branch's (2012)…”
Section: Figure 4 Test Scoresmentioning
confidence: 85%
See 2 more Smart Citations
“…Nevertheless, the studies of Sakai and Kikuchi (2009) revealed 'lack of intrinsic motivation' to be one of the most salient demotivating factors. In addition, a study of Li and Ting (2017) confirmed 'lack of intrinsic motivation' as the most demotivating factor. The findings of Ghadirzadeh and Branch's (2012)…”
Section: Figure 4 Test Scoresmentioning
confidence: 85%
“…However, similar to the findings of present study, Ali and Pathan (2017) suggested a 'one man show' classroom in which students got less chance to speak as demotivating. The findings of Li and Ting's (2017) study also revealed the importance of teachers to pay attention to their teaching methods in order to motivate their students. In this regard, teachers seem to motivate students better when they use communicative teaching methods in the classroom.…”
Section: Demotivating Factors Of Indonesian College Students To Learnmentioning
confidence: 87%
See 1 more Smart Citation
“…However, there are some papers in which DM is used for each isolated application, for instance learner motivation (13% of papers), learning styles (8%), provide feedback for instructors (9%), detecting language anxiety (6%), predicting performance (14%), L2 orientations (8%), language reading comprehension (5%), and detecting grammar issues and assessment (7%). In this analysis, the DM applications most frequently used in the context of FLL are: Predicting performance (Linck et al, 2013;Seker, 2016;Swanson et al, 2016;Wang & Cheng, 2016;Whitehill & Movellan, 2018), learner motivation (Apple, Falout, & Hill, 2013;Li & Zhou, 2017;Saeed et al, 2014;Tajeddin & Moghadam, 2012), provide feedback for instructors (Coskun & Mutlu, 2017;Jiang & Lee, 2017;Kaoropthai, Natakuatoong, & Cooharojananone, 2016;Kieffer & Lesaux, 2012;Rodriguez & Shepard, 2013;Zhao et al, 2015), learning styles (Aslan et al, 2014;Farrington et al, 2015;Hamedi, Pishghadam, & Ghazanfari, 2016;Hsiao, Lan, Kao, & Li, 2017), detecting language anxiety (Baghaei & Ravand, 2015;Cakir & Solak, 2014;Guntzviller et al, 2016;Martin & Valdivia, 2017), and L2 orientations (Allen et al, 2014;Lou & Noels, 2017;Maqsood et al, 2016;Winke, 2013). Figures 8 and 9 show the correlation between the educational level in where the articles mentioned to have developed their proposal and the EDM methods and applications that has been used, respectively.…”
Section: Edm Methods Referencesmentioning
confidence: 99%
“…Research on demotivation has been the foci in second language acquisition in recent decades (Li & Zhou, 2017). For about quarter century, researchers have been working on motivating factors in language learning process and how individuals are motivated as well as focusing on factors that decrease their motivation, or the demotivating factors.…”
Section: Demotivation In Language Learningmentioning
confidence: 99%